Nonconscious Influences from Emotional Faces: A Comparison of Visual Crowding, Masking, and Continuous Flash Suppression - Faivre, Nathan; Berthet, Vincent; Kouider, Sid (Frontiers in Psychology, 2012)
In the study of nonconscious processing, different methods have been used in order to render stimuli invisible. While their properties are well described, the level at which they disrupt nonconscious processing remains unclear. Yet, such accurate estimation of the depth of nonconscious processes is crucial for a clear differentiation between conscious and nonconscious cognition. Here, we compared the processing of facial expressions rendered invisible through gazecontingent crowding (GCC), masking, and continuous flash suppression (CFS), three techniques relying on different properties of the visual system. We found that both pictures and videos of happy faces suppressed from awareness by GCC were processed such as to bias subsequent preference judgments. The same stimuli manipulated with visual masking and CFS did not bias significantly preference judgments, although they were processed such as to elicit perceptual priming. A significant difference in preference bias was found between GCC and CFS, but not between GCC and masking. These results provide new insights regarding the nonconscious impact of emotional features, and highlight the need for rigorous comparisons between the different methods employed to prevent perceptual awareness.